1986
DOI: 10.1002/bjs.1800731007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early blood transfusion on gastrointestinal haemorrhage

Abstract: The effect of citrated stored blood on coagulation was studied initially in a pilot study where 25 patients with acute severe gastrointestinal haemorrhage had their whole blood coagulation measured using the Biobridge Impedance Clotting Time (ICT). This demonstrated that there is a hypercoagulable response to haemorrhage which was partially reversed by blood transfusion. Similar changes were noted in Kaolin Cephalin Clotting Times (KCCT). A further 50 patients were then randomized to receive, during the 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(118 citation statements)
references
References 13 publications
2
112
0
4
Order By: Relevance
“…Hemorrhage results in a hypercoagulable response, 35 which may increase the risk of coronary artery thrombosis. Although postpartum hemorrhage did not remain a significant risk factor in the multivariable analysis, transfusion, a marker of severe hemorrhage, did, with odds Ͼ5-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Hemorrhage results in a hypercoagulable response, 35 which may increase the risk of coronary artery thrombosis. Although postpartum hemorrhage did not remain a significant risk factor in the multivariable analysis, transfusion, a marker of severe hemorrhage, did, with odds Ͼ5-fold.…”
Section: Discussionmentioning
confidence: 99%
“…11 In an experimental animal study, Henriksson and associates 10 noted that the acute loss of 20% of blood volume resulted in a significantly shortened coagulation time, but when such blood loss was followed by transfusion, coagulation time and platelet plug formation time were significantly longer than in non-transfused controls. Blair and colleagues 8 found that, in UGI bleed patients who had received transfusions, clotting times were significantly longer 24 hours after initial presentation. In addition, the proportion of patients experiencing recurrent bleeding before hospital discharge was significantly greater for the transfused group.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] In a study investigating clotting and fibrinolytic markers in patients with UGI bleeding, Henriksson and coworkers 11 found that blood transfusion adversely affected enhanced coagulation. 11 In an experimental animal study, Henriksson and associates 10 noted that the acute loss of 20% of blood volume resulted in a significantly shortened coagulation time, but when such blood loss was followed by transfusion, coagulation time and platelet plug formation time were significantly longer than in non-transfused controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies were small and performed in patient populations other than orthopedic surgery [39][40][41][42][43][44] , or were designed to evaluate outcomes in sickle cell patients 45 ( Table 3). These trials were much too small to evaluate the effect of lower transfusion triggers on clinically important outcomes such as mortality, morbidity, and functional status.…”
Section: Randomized Clinical Trialsmentioning
confidence: 99%